A pharmacovigilance data–driven approach to reveal high fatal adverse events following checkpoint immunotherapy - Zhen Sun; Xuan Deng; Jianglong Guo; Mengsi Liu; Siying Wang; Jian Wang; Jiaojiao Zheng; Kongyan Niu; Weiming Shen; Zhen Ye; Chongming Zheng; Hongye Wang; et al. (Proceedings of the National Academy of Sciences, 2026)
Immune checkpoint inhibitors (ICIs) have significantly improved the outcome of cancer treatment, but they also expose most patients to a variety of treatment-related adverse events (AEs). This study introduces a modified pharmacovigilance approach to identify “ICI-related high-mortality AEs”, a subset of treatment-related complications that are disproportionately reported with elevated fatality during ICI therapy. Utilizing large-scale pharmacovigilance data from 148,972 ICI-treated cases in the FDA AEs Reporting System and 142,645 ICI-treated cases in the WHO global VigiBase, we found 63 types of ICI-related high-mortality AE, such as interstitial lung disease, myositis, and hepatic failure, which necessitate heightened clinical vigilance. Patients who experienced these events had significantly higher fatality reporting rates compared to other cases (36.25% vs. 10.66%). These findings were corroborated in the additional clinical datasets to ensure their generalizability. In summary, identifying these ICI-related high-mortality AEs provides crucial insights for developing proactive monitoring strategies and prioritizes specific events for prevention and intervention to mitigate fatality risk.